The road to entrepreneurship with impairments: A challenges-adaptive mechanisms-results model for disabled entrepreneurs. (December 2019) - Hsieh, Ying-Che; Molina, Victoria Maria Josse; Weng, Jingjing
This article explores how different challenges potentially inspire those deemed impaired to engage with entrepreneurship and how they overcome such challenges through different adaptive mechanisms. Taking an interpretive perspective, we undertook semi-structured interviews with 13 entrepreneurs with impairments, providing an understanding of the relationship between challenges and the adaptive mechanisms that led to business and personal attainments. Based on our empirical findings, we propose a new challenges-adaptive mechanisms-results (CARE) model contributing to the literature on disabled entrepreneurship among those with impairments and also provide insights into the entrepreneurial endeavours of the disabled population.